Coplanar Stripline Loaded Reconfigurable Loop Antenna for WLAN and WiMAX Applications - Shastri, S. P. R.; Singh, R. R.; Ajetrao, K. V. (Engineering, Technology & Applied Science Research, 2018)
In this paper, a loop antenna loaded with coplanar strip (CPS) line is proposed as a multiband antenna. The CPS line is added with two switches to vary the antenna perimeter to cover seven different bands. The CPS line introduced into the loop is not only useful in reconfiguring antenna dimensions but also provides stationary radiation patterns for the all the covered bands. The proposed antenna works in single and dual-band modes. When the proposed antenna works as a single band antenna, it produces a band from 4.2GHz to 5.7GHz. Under dual-band operation, it produces bands from 3.75GHz to 4.7GHz and from 6.4GHz to 7.8GHz. The other dual-band mode ranges from 3.5GHz to 3.8GHz and from 5.58GHz to 7.4 GHz. The simulated and measured results are in good agreement and the proposed antenna can be used satisfactorily for W-LAN and WiMax applications. The proposed technique can also be used for size reduction of loop antennas.